PENGARUH LIKUIDITAS DAN LEVERAGE TERHADAP KEBIJAKAN DIVIDEN TUNAI DENGAN PROFITABILITAS DAN GOOD CORPORATE GOVERNANCE SEBAGAI VARIABEL INTERVENING (Studi Pada Perusahaan Yang Terdaftar di BEI Tahun 2012-2015) - Tri Retno Ningsih, 12.05.52.0244; Jaeni, Jaeni (Students Journal of Accounting and Banking, 2016)
This study examines the effect of liquidity and leverage on dividend policy with profitability and good corporate governance as an intervening variable. This research was conducted on the companies included in the Corporate Governance Perception Index (CGPI) and listed on the Indonesia Stock Exchange (BEI). The sampling method using purposive sampling the study period of 2012 to 2015. The relationship and influence between variables or described by using multiple linear regression analysis and path analysis. The results showed that the liquidity and leverage jointly significant positive effect on profitability. Liquidity no significant negative effect on good corporate governance, while leverage significant positive effect on good corporate governance. Liquidity and leverage jointly not significant positive effect on dividend policy, the profitability of significant positive effect on dividend policy, while the influence of good corporate governance on dividend policy is a significant negative. Liquidity and leverage simultaneous positive effect on dividend policy through profitability and good corporate governance. Â Keywords: Dividend Policy, Profitability, Good Corporate Governance, Liquidity, Leverage